In Situ Respirometric Kinetic Analysis of a Thermophilic Jet Loop Bioreactor - İnce, Mahir; İnce, Elif; Topaloglu, A. (Pleiades Publishing Inc, 2020)
Future liability considerations and stringent regulatory requirements often lead the users to choose end product-driven processes. Over the last decade, high-rate novel reactors have emerged for wastewater treatment, ensuring high removal efficiencies. An example is jet loop reactors offering a number of advantages that could be even further improved by attaining thermophilic conditions. In this study, a respirometric analysis was employed in a thermophilic jet loop reactor for treating potato-processing wastewater in order to determine the kinetic and stoichiometric parameters. The kinetic parameters namely maximum specific growth rate (mu(max)), yield ratio (Y), decay coefficient (k(d)), and half saturation rate constant (K-s) were found to be 0.2 L/h, 0.71 g/g, 0.02 L/h, and 25.72 mg/L, respectively. Bacillus mojavensis, Gordonia paraffinivorans, Bacillus badius and Paenibacillus lactis strains were isolated from the thermophilic jet loop bioreactor. Considering the results, it is recommended that the estimation of kinetic and stoichiometric parameters in this system should preferentially be performed using respirometric techniques.
Keywords: jet loop reactor; kinetic parameters; potato-processing wastewater; respirometric analysis; thermophilic bioreactor